Enzymatic Bioelectrocatalysis - Lojou, Elisabeth; Xiao, Xinxin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Featuring a mild process and high selectivity, enzyme bioelectrocatalysis employing oxidoreductases immobilized on conductive surfaces is playing an increasingly vital role across a wide scope of applications. Enzyme bioelectrocatalysis is key for devices such as biosensors and biofuel cells, which are attracting considerable attention towards sustainable sensing and energy production. A wide range of sophisticated reactions, such as chiral compound synthesis and CO2 and N2 fixation, can be accomplished with enzyme bioelectrocatalysis. Last but not least, redox enzymes are sources of inspiration for new non-noble metal electrocatalysts. The "Enzymatic Bioelectrocatalysis" Special Issue comprises six reviews contributed by research groups from different countries, covering fundamentals and applications, as well as the recent research progress in this field.